Efficient delivery of human clotting factor IX after injection of lentiviral vectors in utero - CHEN Xiao-guang; ZHU Huan-zhang; GONG Ju-li; LI Feng; XUE Jing-lun (Acta Pharmacologica Sinica, 2016)
AIM: To explore gene transfer feasibility for human clotting factor IX (hFIX) mediated by recombinant lentivirus in utero. METHODS: ICR mice fetus at 17-19 d gestation were received lentiviral vectors carrying hFIX cDNA under the control of liver specific promoter by intrahepatic injection. The expression and distribution of hFIX cDNA and possible immune responses against the hFIX were assessed by ELISA, PCR, RT-PCR, and immunohistochemistry, respectively. RESULTS: The serum hFIX protein were detected at different time points in all newborn mice, the highest level of hFIX was 50 microg/L and lasted for more than 30 d. Anti-hFIX antibody was not detected. hFIX cDNA was detected in liver, spleen, and heart. The expression of hFIX cDNA was only detected in liver. Besides, no germ line transmission was found at DNA and RNA levels, and no side effect associated with gene transfer was detected. CONCLUSION: The efficient delivery of hFIX can be achieved by prenatal gene transfer. It thus shows the feasibility of gene therapy for hemophilia in utero.